Clinical implications of disappearing colorectal liver metastases have changed in the era of hepatocyte-specific MRI and contrast-enhanced intraoperative ultrasonography. Issue 8 (August 2018) - Oba, Atsushi; Mise, Yoshihiro; Ito, Hiromichi; Hiratsuka, Makiko; Inoue, Yosuke; Ishizawa, Takeaki; Arita, Junichi; Matsueda, Kiyoshi; Takahashi, Yu; Saiura, Akio
Abstract: Background: Clinical implication of disappearing liver metastases (DLMs) from colorectal cancer after chemotherapy needs to be reviewed in the era of modern imaging studies. Methods: Between 2010 and 2015, 184 patients underwent curative hepatectomy for colorectal liver metastases following preoperative chemotherapy. The sites of metastases detected on pre-chemotherapy CE-CT were examined post-chemotherapy using CE-CT, gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid-enhanced magnetic resonance imaging (EOB-MRI), and contrast-enhanced intraoperative ultrasonography (CE-IOUS). DLMs were defined as tumors that disappeared on CE-CT post chemotherapy. The detection rate of DLMs with EOB-MRI and CE-IOUS were assessed, and the outcome of DLMs resected and those left in place were reviewed. Results: A total of 275 DLMs were noted in 59 patients. On EOB-MRI, 71 lesions (26%) were visible and were resected, 92% (65/71) of which contained viable disease. Using CE-IOUS, an additional 94 lesions were identified. A total of 165 DLMs (60%) were identified and resected by sequential use of EOB-MRI and CE-IOUS, 77% (127/165) of which contained viable disease. Of 110 DLMs not identified, 68 were resected, 4% (3/68) of which contained viable disease. Among 42 lesions left in place, 6 (14%) recurred during the median follow-up period of 27 (9–72) months. Discussion: EOB-MRI and CE-IOUS exploration identified clinically relevant DLMs containing viable disease with a high level of accuracy.